Spatial Variations of Tectonic Uplift - Subducting Plate Effects on the Guerrero Forearc, Mexico - Ramírez-Herrera, María Teresa; Gaidzik, Krzysztof; Forman, Steven L. (Frontiers in Earth Science, 2021)
Uplift is the predominant factor controlling fluvial systems in tectonically deforming regions. Mountains along subduction zones force incision, aggradation or sinuosity modifications, showing differential uplift, variations in erosion rates, in river incision, and in channel gradient produced by ongoing tectonic deformation. Thus, landscape can provide information on the tectonic activity of a defined region. Here, field studies, analysis of geomorphic indices using a digital elevation model, and dating of river terraces, were undertaken to extract: (a) rates of ongoing tectonic deformation, (b) identify evidence of active faulting, and (c) explain the possible relation of ongoing differential uplift in the topography of the overriding plate with the geometry and roughness effects of subducting slab along the Mexican subduction within the Guerrero sector. Landscape analysis using geomorphic indices suggests segmentation along stream of the studied Tecpan River basin. Rates of tectonic uplift were derived from river incision rates computed with the combination of strath terrace heights and associated dating. Tectonic uplift rates vary from ~1 ± 0.3 mm/yr up to ~5± 0.6 mm/yr during the Holocene, consistent with inferred high tectonic activity in this zone. These results vary significantly spatially, i.e. increasing upstream. Possible explanations for spatial variations of tectonic uplift rates are most likely related to an effect of the geometry and the rugged seafloor of the oceanic Cocos plate subduction beneath a faulted continental lithosphere.